(untitled) (Scientific journal of the Fergana State University, 2023)
The article analyzes the fate of women in the works of English writers of the Victorian period. During this period writers such as C. Dickens, Sisters Bronte, E. Gaskell, J. Eliot described the fate of women in their works in different ways.